ERGOTHERAPY IN RHEUMATOLOGY - Tat’yana Vladimirovna Dubinina; M L Sukhareva; Sh F Erdes (Научно-практическая ревматология, 2014)
The article reports one of the most affordable rehabilitation methods, i.e. occupational therapy. The issues related to the history of occupational therapy as a treatment method, its application in rheumatology and promising directions of development are covered.